Study of electromagnetic emissions associated with seismic activity in Kamchatka region - Gladychev, V.; Baransky, L.; Schekotov, A.; Fedorov, E.; Pokhotelov, O.; Andreevsky, S.; Rozhnoi, A.; Khabazin, Y.; Belyaev, G.; Gorbatikov, A.; Gordeev, E.; Chebrov, V.; et al. (Natural Hazards and Earth System Sciences, 2001)
A review of data processing of electromagnetic emission observation collected at the Complex Geophysical Observatory Karimshino (Kamchatka peninsula) during the first 5 months (July–November, 2000) of its operation is given. The main goal of this study addresses the detection of the phenomena associated with Kamchatka seismic activity. The following observations have been conducted at CGO: variations of ULF/ELF magnetic field, geoelectric potentials (telluric currents), and VLF signals from navigation radio transmitters. The methods of data processing of these observations are discussed. The examples of the first experimental results are presented.